"Address me personally!": On the role of language styles in a MOOC. (7th June 2018) - Riehemann, J.; Jucks, R.
Abstract: If learning materials are presented in either a conversational or formal language style, people will process them differently. This study reports an experiment in which 64 high school students watched an educational video in a massive open online course scenario in which the instructions were phrased either conversationally or formally. The video demonstrated and explained the psychological McGurk effect. After watching the video, participants performed a transfer task. Learning outcomes were assessed and answers were analysed by using Linguistic Inquiry and Word Count. Results showed better learning outcomes for participants in the conversational (vs. formal) condition. Participants in the formal (vs. conversational) condition referred more to others in their answers. Implications for the design of massive open online courses are discussed. Lay Description: What is currently known about the subject matter: Language styles can affect individual dealing with learning materials. Addressing learners directly in the learning material can support transfer performance. Massive open online courses (MOOCs) have become the most prominent form of online learning in higher education. High school students (future students) are a new group of MOOC users. What this paper adds: MOOCs contain a social dimension, which might be crucial for individual learning. Most MOOCs do not ask for transferring knowledge of just learned materials. Conversational language in the instruction led to better transfer performance and more self‐directedness. Instructional language styles affect individual dealing with learning materials in a MOOC scenario. Implications of study findings for practitioners: MOOCs should apply conversational language style instructions for deeper learning. Conversational language style instructions and transfer tasks are easy to implement in already existing MOOCs. Being personally addressed in a MOOC might be a key for enhancing learners' involvement.